2011
DOI: 10.4025/actascianimsci.v33i4.12629
|View full text |Cite
|
Sign up to set email alerts
|

Silagem de capim-elefante aditivada com produtos alternativos

Abstract: RESUMO. Objetivou-se avaliar o padrão de fermentação e a composição bromatológica da silagem de capim-elefante utilizando diferentes aditivos. Utilizou-se o delineamento inteiramente casualizado com seis tratamentos (capim-elefante sem aditivo; com 100 kg de farelo de arroz t . Com a exceção do inoculante bacteriano, todos os aditivos proporcionaram aumento nos teores de matéria seca (27,95 a 31,65%) e carboidratos solúveis (15,20 a 17,14%) na forragem a ser ensilada. Os aditivos promoveram adequado padrão de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 13 publications
1
13
1
13
Order By: Relevance
“…[11] explained that proteolysis is extended during fermentation when acidic conditions are not sufficient for inhibiting undesirable microorganisms. Similar results were obtained by [18], who evaluated elephant grass silage and observed that low CP concentrations occurred in silage without additives due to the loss of soluble nitrogenated compounds in the effluent. However, at the 8%, 16%, 24% and 32% levels, the lowest concentrations were obtained from the maize and sorghum brans (P < 0.05), which differed from the millet and wheat brans.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…[11] explained that proteolysis is extended during fermentation when acidic conditions are not sufficient for inhibiting undesirable microorganisms. Similar results were obtained by [18], who evaluated elephant grass silage and observed that low CP concentrations occurred in silage without additives due to the loss of soluble nitrogenated compounds in the effluent. However, at the 8%, 16%, 24% and 32% levels, the lowest concentrations were obtained from the maize and sorghum brans (P < 0.05), which differed from the millet and wheat brans.…”
Section: Resultssupporting
confidence: 73%
“…At the 24% and 32% levels, the N-NH 3 /NT concentrations for all of the brans were between 2.87% and 2.02%. These results were greater than the results that were obtained by [18], in which elephant grass silage was evaluated. These authors identified average N-NH 3 /NT concentrations of 3.95% following the addition of rice bran, soybean hulls, maize flour and sugar cane.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…This is due the lower cost per ton of DM obtained with these silages, corroborating the economic results obtained in the present work. In view of the greater competitiveness of livestock farming in relation to agriculture through land use, and aiming at better remuneration over invested capital, we have sought complementary production technologies that provide integrated benefits to the production system as a whole (Monteiro, Abreu, Cabral, Ribeiro, & Reis, 2011). Thus, as suggested by Vieira et al (2010), the agronomic management of crop to obtain satisfactory nutritive value and with high-yielding pastures would justify the use of this forage as a preserved food, allied to the process of intensification of meat and milk production in pastures.…”
Section: Resultsmentioning
confidence: 99%
“…O uso do milho moído tem sido descrito como um aditivo importante na melhora da qualidade fermentativa e bromatológica de silagem de capim-elefante e também em outras forrageiras (Andrade et al, 1998;Monteiro et al, 2011). Seu uso é justificado principalmente para suprir alguma deficiência característica da forrageira ensilada.…”
Section: Introductionunclassified